Neuroimaging and Electroencephalographic Correlation in Patients with Transient Global Amnesia: Clinical Case Series. (May 2023) - Theodorou, Georgios-Theofilos; Psoma, Elisavet; Terzoudi, Aikaterini; Mavropoulou, Xanthipi; Roilidis, Ioannis; Vadikolias, Konstantinos; Spilioti, Martha
Objective . To determine if there is any correlation between the electroencephalographic and neuroimaging findings in patients with Transient Global Amnesia (TGA).Methods: We retrospectively reviewed files of the First Department of Neurology of AHEPA University Hospital, including patients with a clinical diagnosis of TGA. Only patients who had the characteristic high signal in the temporal lobes in the DWI MRI and those who underwent electroencephalographic recording (EEG) were selected.Results: Out of 28 patients, 8 were selected. We found that 6 out of 8 patients (75%) who had imaging findings in DWI, in at least one medial temporal lobe, also had had intermittent slow theta waves on the electroencephalographic recording. Of these 6 patients, 3 (50%) had bilateral EEG findings, 2 patients (33, 3%) only had findings on the left hemisphere and 1 (17%) had on the right hemisphere. 3 out of 6 patients (50%) had electroencephalographic dominance on the left, while 2 out of the 6 (33%) had on the right. In 2 patients with imaging findings in DWI no anomalies were demonstrated on EEG. In 3 out of 8 patients, both MRI and EEG findings correlated on the same side, while 1 patient had opposite findings, depending on which hemisphere the EEG anomalies dominated.Conclusions: There is no absolute matching between the DWI MRI and EEG findings in patients with the clinical diagnosis of TGA. However, there is some degree of correlation, when we focus on the focal dominance of the EEG anomalies, although not statistically significant.